(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of this paper is to explore and calculate the hosting capacity in power system to determine the maximum renewable energy resources that will be spread. After the distributed generation (DG) is connected to the distribution systems, the performance indicator of the distribution system will get better or deteriorate. The point that between acceptable degradation and unacceptable degradation is the hosting capacity. This paper is exactly concerned with the influence of maximizing DG on the performance index in radial distribution networks (RDN) and else finding the maximum point of the suitable deterioration. Hosting capacity is the total amount of distribution generation that will be added to the radial distributed network without the need for other upgrades in the networks. This paper introduces a new proposed algorithm to calculate the hosting capacity and determine the quantities of DG that can be added to distributed networks before the voltage at the bus, the current through cables or the power fed back to the substation or quality or system reliability for consumers override their maximum allowed value . The two main boundaries for finding the hosting capacity are overload and overvoltage. The objective function is studied for finding the maximum hosting capacity (MHC). by inserting maximum hosting capacity of distribution generation (DG) on the 33 IEEE- standard networks taking into consideration the over voltage and thermal limit. in this study the DG is Photovoltaic (PV) for different load level